Numerical Modelling of Seismic Behavior of Retrofitted RC Beam-Column Joints - Seyyed Aliasghar Arjmandi; Maryam Yousefi (Salehan Institute of Higher Education, 2018)
In the event of an earthquake, the beam-column joints in the reinforced concrete moment-resisting frame structures are affected by a high level of deformations and stresses. Due to these deformations and stresses, the joint can be damaged and even fractured in some cases. The failure of the beam-column joint can cause the building to collapse. In recent years, particular attention has been paid to strengthening joints in the substandard RC buildings. In this paper, the beam-column joint is investigated considering the nonlinear behavior for concrete and steel. For concrete, the damage plasticity model and for reinforcing steels bilinear plasticity model is used. Several examples of tested joints in the technical literature have been modeled before and after strengthening, then numerical and experimental results are compared. Seismic performance of joints has also been studied. The results of this research show good agreement between the results of finite element model and experimental results. Moreover, the retrofitting method have shown could improves the seismic performance of the joint.